Pengaruh Kualitas Produk Dan Promosi Terhadap Keputusan Pembelian (Studi Kasus pada Usaha Dagang Keripik Buah “Mekar Sari” di Desa Tlogo III, Kecamatan Kanigoro, Kabupaten Blitar) - Riska Nindia Sari; Wulan Destari Natalia (Universitas Islam Balitar, 2021)
Trading business is able to win the competition if it can have products according to customer wants and needs and can convey the advantages of its products to consumers. There are several aspects that can influence consumer decision making to buy products, including quality products and company promotion activities. This exploration was directed at the